MANFAAT BATANG PISANG DAN AMPAS TAHU SEBAGAI PAKAN KONSENTRAT TERNAK SAPI - Ayu Novtiana Devri; Handoko Santoso; Muhfahroyin Muhfahroyin (BIOLOVA, 2020)
Abstract: Cattle feed consists of forage and reinforcement feed (concentrate), forage feed is all feed material derived from plants or plants in the form of leaves, sometimes including stems, twigs and flowers. Banana stems and tofu dregs can be used as concentrated feed ingredients for cows, because it has the benefit of banana stems having a fairly good nutritional value of 87.7% content of dry nutrients (BK), ash 25.12%, crude fat ( LK) 14.23%, crude fiber (SK) 29.40%, crude protein (PK) 3.01% and extract without nitrogen (BETN) 28.24%. While tofu waste contains 8.66% protein, 3.79% fat, 51.63% water, and 1.21% ash.